2020
DOI: 10.1007/s40618-020-01452-w
|View full text |Cite
|
Sign up to set email alerts
|

Adverse pathophysiological influence of early testosterone therapy on the testes of boys with higher grade sex chromosome aneuploidies (HGAs): a retrospective, cross-sectional study

Abstract: Purpose Higher grade aneuploidies (HGAs) of the male sex chromosomes are a rare genetic group of pathologies caused by nondisjunction meiotic events. The aim of this study was to evaluate the impact of early androgenic therapy on the testicular secretory hormone profile, and the pathophysiological implications. Patients and methods In this cross-sectional study, 18 HGA subjects aged 6–8 years were recruited. They were divided into two groups, based on whether or not they had previously undergone testosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Testosterone treatment includes different strategies, based on the age of patient: early hormonal treatment (EHT), from 4 to 60 months of age; hormonal booster treatment (HBT), from 5 to 8 years of age and finally testosterone replacement therapy (TRT), from puberty to the rest of life [ 21 ]. Patients with high grade aneuploidies that underwent an early treatment with testosterone show persistent suppression of testicular secretory function [ 53 ]. In 2020, Gropman et al [ 17 ], demonstrated that affected patients treated with HRT obtained higher scores on the Bayley Scales of Infant Development (BSID-III), compared with untreated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone treatment includes different strategies, based on the age of patient: early hormonal treatment (EHT), from 4 to 60 months of age; hormonal booster treatment (HBT), from 5 to 8 years of age and finally testosterone replacement therapy (TRT), from puberty to the rest of life [ 21 ]. Patients with high grade aneuploidies that underwent an early treatment with testosterone show persistent suppression of testicular secretory function [ 53 ]. In 2020, Gropman et al [ 17 ], demonstrated that affected patients treated with HRT obtained higher scores on the Bayley Scales of Infant Development (BSID-III), compared with untreated patients.…”
Section: Discussionmentioning
confidence: 99%
“… 66 68 These results cannot be applied to patients with higher grade sex chromosome aneuploidies, such as 48, XXXY, 48, XXYY or 49, XXXXY, in whom testosterone treatment resulted in an earlier and persistent suppression of testicular hormone production. 103 …”
Section: Pharmacotherapy For Male Hypogonadismmentioning
confidence: 99%
“…[66][67][68] These results cannot be applied to patients with higher grade sex chromosome aneuploidies, such as 48, XXXY, 48, XXYY or 49, XXXXY, in whom testosterone treatment resulted in an earlier and persistent suppression of testicular hormone production. 103 One study assessed the effect of r-FSH treatment on 3 boys with central hypogonadism. 12 The underlying rationale was that FSH is important to provoke Sertoli cell proliferation before pubertal maturation induced by intratesticular testosterone.…”
Section: Pharmacotherapy In Childhoodmentioning
confidence: 99%